2009
DOI: 10.1097/jto.0b013e3181b68e5a
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate Use in Patients with Lung Cancer and Bone Metastases: Recommendations of a European Expert Panel

Abstract: The panel recommends screening patients with lung cancer for bone metastases at the initial staging of disease to assess symptomatic bone metastases and screen for asymptomatic bone metastases and to allow accurate monitoring of bone disease progression and initiate bone-specific therapy. Bone assessment should be based on positron emission tomography (if available) or bone scan. BPs should be added to the treatment of patients with lung cancer (with non-small cell lung cancer or small cell lung cancer) who de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 71 publications
(72 reference statements)
0
39
0
Order By: Relevance
“…The use of biphosphonates for delaying or preventing the development of SRE in lung cancer patients with bone metastasis is strongly recommended [33]. In the present study, when zolendronic acid was compared with placebo, in patients receiving zoledronic acid, median time to development of first SRE was prolonged (5.6 vs 5.0 months, respectively), and zoledronic acid delayed the appearance of SRE in patients with NSLCL.…”
Section: Discussionmentioning
confidence: 55%
“…The use of biphosphonates for delaying or preventing the development of SRE in lung cancer patients with bone metastasis is strongly recommended [33]. In the present study, when zolendronic acid was compared with placebo, in patients receiving zoledronic acid, median time to development of first SRE was prolonged (5.6 vs 5.0 months, respectively), and zoledronic acid delayed the appearance of SRE in patients with NSLCL.…”
Section: Discussionmentioning
confidence: 55%
“…The benefit of bisphosphonate treatment in the NSCLC population with bone metastasis is well documented, and bisphosphonate treatment for lung cancer with bone metastasis has been strongly recommended to prevent and delay SREs [4,25]. However, in our study population only a very small proportion of patients (6.6%) received bisphosphonate (pamidronate or zoledronic acid) for primary prevention of SRE.…”
Section: Discussionmentioning
confidence: 91%
“…Many clinical studies in which urinary NTx levels were used as a marker have been reported in the past [13][14][15]; however, we were unable to find examples of studies of serum NTx. In our study, the results clearly indicate that serum NTx levels are more closely related to bone metastasis than to ALP or LDH, which have been said to become elevated during bone metastasis [16,17].…”
Section: Discussionmentioning
confidence: 88%